The Challenge of Internet Literacy: The Instruction-Web Convergence, 1st edition - Martin, Lyn Elizabeth M. (Routledge, 2020)
This book, first published in 1997, gives an overview of how the Internet is used in academic libraries, with a focus on the dual role librarians serve as instructors and researchers. It includes concise summaries, keyword listings, and up-to-date bibliographies for each chapter. It contains in-depth coverage of, among others: a research planning process that leads searchers to logical sources on the web and a systematic analysis of the results; a case study from the University of Texas at Austin that shows how to integrate information literacy skills into traditional services and partnerships; the development of a web page by a government documents department and a navigational tool developed by a physics laboratory; and identification and evaluation of internet resources for test and measurement tools for education and psychology and a selected bibliography listing resources for internet trainers.